LEARNING VISUAL ARTS CREATION FOR CHILDREN WITH AUTISM AT SLB NEGERI PATI, INDONESIA - Febriana, Nia Prawista; Syafii (Eduarts: Jurnal Pendidikan Seni, 2025)
This study discusses two-dimensional art learning for autistic children at SLB Negeri Pati. The objectives of this research are to describe the process of learning two-dimensional art creation for autistic children, describe the two-dimensional artworks created by autistic children through art learning at SLB Negeri Pati, and identify supporting and inhibiting factors in the implementation of two dimensional art learning for autistic children at SLB Negeri Pati. The research method used is descriptive with techniques of observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The study shows that two-dimensional art learning is carried out through RPP (lesson plan) which includes planning, implementation, and assessment. The results include painting, collage, and graphic art with techniques such as plakat, collage, and stamping. Video media and demonstration techniques help children develop their skills in expressing imagination. Supporting factors include adequate facilities, student enthusiasm, and teacher support, while inhibiting factors stem from the difficulty autistic children face in controlling their mood, which leads to boredom and incomplete task completion.